The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/jcm12062327
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Surgical Outcome Risk Tool (SORT) and SORT v2 for Predicting Postoperative Mortality in Patients with Pancreatic Cancer Undergoing Surgery

Abstract: Background: Pancreatic cancer surgery is related to significant mortality, thus necessitating the accurate assessment of perioperative risk to enhance treatment decision making. A Surgical Outcome Risk Tool (SORT) and SORT v2 have been developed to provide enhanced risk stratification. Our aim was to validate the accuracy of SORT and SORT v2 in pancreatic cancer surgery. Method: Two hundred and twelve patients were included and underwent pancreatic surgery for cancer. The surgeries were performed by a single s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Therefore, the recommended optimal interval for pancreatic surgery after infection in our study is 4 weeks, different from the recent consensus, which suggests a recommended timing of 7 weeks, 8 based on a baseline validated risk assessment tool. 26 Our conclusions are derived from a prospective observational cohort study focusing on pancreatic surgery rather than overall surgery. In addition, our study was conducted during a different phase of the pandemic, when most of the enrolled patients may have been infected with a less toxic variant of Omicron and thus, had milder symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the recommended optimal interval for pancreatic surgery after infection in our study is 4 weeks, different from the recent consensus, which suggests a recommended timing of 7 weeks, 8 based on a baseline validated risk assessment tool. 26 Our conclusions are derived from a prospective observational cohort study focusing on pancreatic surgery rather than overall surgery. In addition, our study was conducted during a different phase of the pandemic, when most of the enrolled patients may have been infected with a less toxic variant of Omicron and thus, had milder symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…It can address the current limitations in available platforms and ensure that the complexity and specific considerations of HPB surgeries are adequately reflected in the assessment, potentially leading to more accurate cost evaluation and resource allocation. According to a recent study from our team [6], the SORT has demonstrated excellent discrimination (area under the curve: 0.98) and calibration traits in predicting 30-day mortality regarding patients undergoing pancreatic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Based on increasing evidence favoring the use of multiple arterial conduits in patients undergoing CABG [11], a "Hegelian" circle, based on the superiority of the MAG approach, is about to close, and a new one is about to open, which will examine different strategies in conduits harvesting, treatment protocols on the extent of target vessel stenosis for radial artery conduits, along with post-discharge treatment protocols. The present Special Issue includes several articles that aim to answer important debates on different perioperative treatment pathways [12][13][14][15][16][17][18]. Two of them [14,15] validate risk-stratification tools, thus providing a necessary insight into preoperative planning and patient counseling while enhancing the shared decision-making process.…”
mentioning
confidence: 99%
“…Dr. Richard Prager is a characteristic world-historical individual in the field of QI in cardiothoracic surgery. From the very beginning of his efforts to establish a QI program in the State of Michigan, Dr. Prager faced certain great challenges, such as a) gathering all cardiothoracic surgeons of the State around a common table to discuss their outcomes and designing QI initiatives, The present Special Issue includes several articles that aim to answer important debates on different perioperative treatment pathways [12][13][14][15][16][17][18]. Two of them [14,15] validate risk-stratification tools, thus providing a necessary insight into preoperative planning and patient counseling while enhancing the shared decision-making process.…”
mentioning
confidence: 99%
See 1 more Smart Citation